The proteome of the human endolymphatic sac endolymph - Ölander, Christine (Sci Rep, 2021)
The endolymphatic sac (ES) is the third part of the inner ear, along with the cochlea and vestibular apparatus. A refined sampling technique was developed to analyse the proteomics of ES endolymph. With a tailored solid phase micro-extraction probe, five ES endolymph samples were collected, and six sac tissue biopsies were obtained in patients undergoing trans-labyrinthine surgery for sporadic vestibular schwannoma. The samples were analysed using nano-liquid chromatography-tandem mass spectrometry (nLC-MS/MS) to identify the total number of proteins. Pathway identification regarding molecular function and protein class was presented. A total of 1656 non-redundant proteins were identified, with 1211 proteins detected in the ES endolymph. A total of 110 proteins were unique to the ES endolymph. The results from the study both validate a strategy for in vivo and in situ human sampling during surgery and may also form a platform for further investigations to better understand the function of this intriguing part of the inner ear.